2020
DOI: 10.26656/fr.2017.4(s6).057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different pasteurisation temperature on physicochemical properties, bioactive compounds, antioxidant activity and microbiological qualities of reconstituted pomegranate juice (RPJ)

Abstract: Reconstituted pomegranate juice (RPJ) was thermally treated with high-temperature pasteurisation (HTP) at 95°C and mild-temperature pasteurisation (MTP) at 80°C for 30 s respectively. As a comparison, the effect on physicochemical properties, including antioxidant activities and microbial inactivation was eavluated. Both MTP and HTP showed effective inactivation of microbial growth to negligible level with MTP taking almost half pasteurisation-time (-46.3%) as compared to HTP, indicating possible less energy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The mixture was heated to 95 °C for 30 seconds and subsequently cooled to 40 °C. The high temperature was used for heating since this enabled the release of membrane-bound phenolic content in the juice following the study by Kong et al (2020). Finally, vitamin C was fortified by adding vitamin C into the cooled mixture, reducing the pH from 4.11 to 3.20. pH below four was found to help slow down microbial growth, as evidenced by the study conducted by Kong et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mixture was heated to 95 °C for 30 seconds and subsequently cooled to 40 °C. The high temperature was used for heating since this enabled the release of membrane-bound phenolic content in the juice following the study by Kong et al (2020). Finally, vitamin C was fortified by adding vitamin C into the cooled mixture, reducing the pH from 4.11 to 3.20. pH below four was found to help slow down microbial growth, as evidenced by the study conducted by Kong et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The high temperature was used for heating since this enabled the release of membrane-bound phenolic content in the juice following the study by Kong et al (2020). Finally, vitamin C was fortified by adding vitamin C into the cooled mixture, reducing the pH from 4.11 to 3.20. pH below four was found to help slow down microbial growth, as evidenced by the study conducted by Kong et al (2020). The mixture was then poured into molds, and as it cooled further, it began to set and take the shape of the molds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At pasteurization temperature and time were 85 o C and 30 minutes, the color parameters of product had suitable values that the making to product was good color. According to Kong et al [32], the pasteurization changed color parameters of pomegranate juice, it increased a * value, decreased b * and L * values while E values did not change significantly. In addition, a study of Buniowska et al [33] showed that there were an increasing of L * and b * values, and decreasing of a * value after heating fruit beverages.…”
Section: Effect Of Pasteurization Temperature and Time On Color Param...mentioning
confidence: 98%